Ecological traits shape genetic diversity patterns across the Mediterranean Sea: a quantitative review on fishes. (17th November 2015) - Dalongeville, Alicia; Andrello, Marco; Mouillot, David; Albouy, Camille; Manel, Stéphanie
Abstract: Aim: We set out to identify the determinants of the variation in genetic diversity among fish species and test whether multi‐species genetic diversity is randomly distributed in space. Location: Mediterranean Sea. Methods: We collected genetic diversity data from 39 published studies on Mediterranean fishes (31 species) along with the spatial coordinates of the sampling sites. We focused on microsatellite heterozygosity (151 data points) and mitochondrial haplotype diversity (201 data points). We used linear regressions to link genetic diversity and 11 ecological traits. We also tested for spatial autocorrelation and trends in the residuals. Results: Among‐species variation in microsatellite heterozygosity was explained by three ecological traits: vertical distribution, migration type and body length. Variation in mitochondrial haplotype diversity was also explained by vertical distribution and migration type, and by reproductive strategy (semelparity). However, vertical distribution and migration type showed opposite effects on microsatellites and mitochondrial diversity. After accounting for the effects of ecological traits, no spatial pattern was detected, except for one of the species considered. Main conclusions: Ecological factors explain an important proportion of the among‐species genetic diversity. These results suggest that life history strategies of the species influence the variation of microsatellite diversity indirectly through their effect on effective population size, while the spatial variations of genetic diversity seem to be too complex to be identified in our analysis. We found very different effects of traits on mitochondrial and nuclear DNA diversity, which can be explained by the specificities of mitochondrial DNA (absence of recombination, maternal inheritance and non‐neutrality).